Strategi Pembelajaran yang Menyenangkan dan Bermakna untuk Anak Usia Dini - Lisya Nur Aini; Nasywa Ayu Kandias; Riza Melani Riza; Maharani Maharani (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2025)
This research employed a descriptive qualitative approach with data collected through a three-dayobservation conducted on May 5, 6, and 7, 2025. The study subjects consisted of 40 early childhood learnerswho participated in thematic learning on “Fruits.” Activities included recognizing and touching fruit textures,weighing fruits (Day 1); identifying fruit tastes, searching for fruit cards, and making fruit collages (Day 2); aswell as washing and eating fruits together (Day 3). Each activity was designed to stimulate various aspects ofchild development, including cognitive, language, fine motor, gross motor, and social-emotional domains. Theresults revealed that the implemented strategies successfully created a fun and meaningful learning atmosphere.Children appeared enthusiastic, actively involved, able to collaborate in groups, and demonstratedunderstanding of the material. Learning activities based on real-life experiences and participation provedef ective in increasing interest and comprehension among children. The group-based learning also fosteredchildren's social abilities through cooperation, communication, and mutual assistance. Thus, fun andmeaningful learning strategies can be considered appropriate approaches to improve the quality of earlychildhood education. Teachers are encouraged to design learning activities that are not only informative but alsocontextual, emotionally engaging, and rooted in the real-life experiences of children.